Pengaruh Self-efficacy Terhadap Keterlibatan Siswa Melalui Motivasi Belajar - Nurrindar, Mareta; Wahjudi, Eko (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The purpose of this research is to determine the role of learning motivation as a variabele that mediates effect of self-efficacy on student involvement in students Accounting and Financial Institution departement of SMK IPIEMS Surabaya. The population in this research amounted to 81 students Accounting and Financial Institution department of SMK IPIEMS Surabaya, whose entire population was used as the sample. Data obtained from a questionnaire as a measuring tool. Data analysis technique used is a data analysis technique SEM (Structural Equation Modeling) using WarpPLS software version 7.0, with two sub-models: outer model and inner model. Conclusion from the result of this study is that there is a significant direct positive influence between self-efficacy on student involvement, indicating that there is a significant positive direct effect between learning motivation on student involvement, and shows that there is a significant positive direct effect between self-efficacy on student learning motivation Department Accounting and Financial Institution of SMK IPIEMS Surabaya, and there is a significant positive indirect effect between self-efficacy on student engagement with learning motivation mediating variable in students Accounting and Financial Institution departement of SMK IPIEMS Surabaya.